Static and dynamical manifestations of Hamiltonian monodromy - Delos, J B; Schleif, C R; Dhont, G (Journal of physics. Conference series, 2008)
The word monodromy means once around a course , and it refers to changes that might occur when a system goes around some closed loop [1]. We discuss here a phenomenon whose proper name is nontrivial monodromy of action and angle variables in a Hamiltonian system ; for the obvious reason, we just call it Hamiltonian monodromy . In this paper we describe two manifestations of Hamiltonian monodromy: a manifestation in a time-dependent classical system, and a manifestation in a stationary quantum system. Then we give a brief description of the mathematical theory, and finally close with a short survey of previous work on this subject.